Norma ISO 9001/2000 como modelo de gestão: um roteiro de implantação para as organizações e sua implementação - um estudo de caso - Felin, Renata Saurin (2007)
In a global market with increasing demands of customers, the establishment and maintenance of quality management systems and their subsequent certification is in a critical factor of success for organizations wishing to improve their performance, optimizing their processes and resources and, therefore, by increasing their productivity and competitiveness. It should be emphasized that the deployment itself is a process of learning and therefore should not have very strict rules, but be adapted to the culture of the company. In this context, the present study proposes to develop a road map for implementation of a quality management system based on the requirements of ISO 9001:2000. Use as a basic methodological analysis through case study and the interpretation family ISO 9000 rules. For that, initially, is the established theoretical basis of the work and, interpretation of the requirements of ISO 9001:2000. Then defines the steps to achieve certification on the basis of case studies. So then, is an analysis of the implementation of ISO 9001:2000 using the roadmap proposed. In conclusion, it is considered that the greatest challenge in the implementation of the Quality Management System in the company under study is the change in the culture of people of the organization. These stages are understanding that the implementation of a management system brings positive reflections on various aspects such as increased productivity, higher quality products, access to new markets, attention to legal requirements credibility of customers, among others. Therefore, the proposed roadmap is appropriate to the organization and it is recommended to other organizations specifically in the area of industry.